2010
DOI: 10.1039/c004218h
|View full text |Cite
|
Sign up to set email alerts
|

Flexible and enantioselective access to jaspine B and biologically active chain-modified analogues thereof

Abstract: Whereas the all-cis tetrahydrofuran framework of the cytotoxic anhydrophytosphingosine jaspine B is considered as a relevant pharmacophore, little is known about the influence of the aliphatic chain of this amphiphilic molecule on its activity. We developed a synthetic strategy allowing flexible introduction of various lipophilic fragments in the jaspine's skeleton. The route was validated with two distinct approaches to jaspine B. Five chain-modified analogues were also prepared. Biological evaluation of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…Late-stage introduction of the side-chain makes it easy to synthesize derivatives bearing various side chains at the C-2 position. 7,16,27) To construct the cyclic structure of 5, we planned to employ cyclization of monotosylate 7. Compound 7 would be obtained from 1,2,4-triol 9 via selective tosylation of the primary alcohols catalyzed by dibutyltin oxide (Bu 2 SnO).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Late-stage introduction of the side-chain makes it easy to synthesize derivatives bearing various side chains at the C-2 position. 7,16,27) To construct the cyclic structure of 5, we planned to employ cyclization of monotosylate 7. Compound 7 would be obtained from 1,2,4-triol 9 via selective tosylation of the primary alcohols catalyzed by dibutyltin oxide (Bu 2 SnO).…”
Section: Resultsmentioning
confidence: 99%
“…6) Andrieu-Abadie and colleagues also reported that 1 induces apoptosis in murine B16 melanoma cells through an increase in intracellular ceramide levels resulting from inhibition of the activity of sphingomyelin synthase. 7,8) Moreover, 1 was demonstrated to inhibit several kinases such as sphingosine kinase (SphK), cyclin-dependent kinase 2, and extracellular regulatory kinase. 9,10) Because of its novel structural features and impressive biological activity, many total syntheses of 1 have been accomplished.…”
mentioning
confidence: 99%
See 3 more Smart Citations